1996
DOI: 10.1007/bf00035274
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic variation in somatic tissue cultures and regenerated plants of barley (Hordeum vulgare L.)

Abstract: Chromosome number of morphogenic and non-morphogenic calli and regenerated plants of barley were determined. Cultures were obtained from two kinds of explants, immature embryos and seedling leaves from three cultivars, Ingrid, Dissa and Golden Promise. Callus chromosome analyses were carried out during a 12 month period in a medium containing 2 mg/1 of 2,4-D. Diploid cells were predominant in all cases; although in leaf-derived cultures tetraploid cells (2n --4x --28) showed a tendency to increase as time in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Gonzalez et al (1996) suggested that the source of explant, the type of callus (morphogenie vs. non-morphogenic) and duration of culture was more important than the genotype in determining chromosomal stability of barley cultures. Gonzalez et al (1996) suggested that the source of explant, the type of callus (morphogenie vs. non-morphogenic) and duration of culture was more important than the genotype in determining chromosomal stability of barley cultures.…”
Section: Origin Of Somaclonal Variationmentioning
confidence: 99%
“…Gonzalez et al (1996) suggested that the source of explant, the type of callus (morphogenie vs. non-morphogenic) and duration of culture was more important than the genotype in determining chromosomal stability of barley cultures. Gonzalez et al (1996) suggested that the source of explant, the type of callus (morphogenie vs. non-morphogenic) and duration of culture was more important than the genotype in determining chromosomal stability of barley cultures.…”
Section: Origin Of Somaclonal Variationmentioning
confidence: 99%